Preparation method of positive active material, positive active material, positive plate and battery
The preparation of the positive electrode active material with LiNbO3 and Li2WO4 coatings by one-step calcination method has solved the problems of complex and poor performance of the existing lithium manganate composite material preparation methods, and achieved improvements in battery capacity and circulation performance.
Patent Information
- Application Number
- CN202411722635.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The existing lithium manganate composite materials have complex processes, high coating thickness and poor uniformity, resulting in poor battery capacity and rate performance.
By mixing the manganese precursor, lithium source, W source, Nb source and metal M source uniformly through one-step calcination method, a positive electrode active material with LiNbO3 and Li2WO4 coating layers was prepared to achieve a combination of doping and coating.
The process flow is simplified, the cost is reduced, the lattice structure of lithium manganate is stabilized, the capacity and circulation performance of the battery is improved, and the rate performance is improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery production, and in particular to a method for preparing a positive electrode active material, a positive electrode active material, a positive electrode sheet, and a battery. Background Art
[0002] Compared with other rechargeable battery systems, lithium-ion secondary batteries have the advantages of high operating voltage, light weight, small size, no memory effect, low self-discharge rate, long cycle life, and high energy density. They are currently widely used in mobile phones, laptops, tablet computers, electric vehicles, energy storage grids, etc. In recent years, with the rapid development of electric vehicles, people have higher demands for battery energy density, safety, cost and environmental protection.
[0003] Lithium manganese oxide has attracted widespread attention due to its abundant resources and low price. However, there are a large number of trivalent manganese ions in lithium manganese oxide, which are prone to side reactions with the electrolyte, causing the battery's cycle performance to deteriorate. The preparation method of lithium manganese oxide composite materials in the prior art is generally to dope first and then coat, and the process is relatively complicated. In addition, the thickness of the coating layer formed is relatively high and the uniformity is poor, which is not conducive to the battery's capacity performance and rate performance. Summary of the invention
[0004] In order to solve the above technical problems, the present invention discloses a method for preparing a positive electrode active material, a positive electrode active material, a positive electrode sheet, and a battery. The technical solution of the present invention is implemented as follows:
[0005] The first aspect of the present invention is to provide a method for preparing a positive electrode active material, the method comprising the following steps:
[0006] S1, mixing a manganese-containing precursor, a lithium source, a W source, a Nb source and a metal M source uniformly to obtain a mixture;
[0007] S2. calcining the mixture to obtain a positive electrode active material.
[0008] In some embodiments, in step S1 , the W source is tungsten oxide.
[0009] In some embodiments, in step S1 , the metal M source includes at least two metal elements.
[0010] In some embodiments, the metal elements include at least two of Mg, Al, Ca, Ti, Cu, Zn, Y, Zr, Ru, Sn, and Sb;
[0011] In some preferred embodiments, the metal elements include at least two of Al, Mg, Sn, and Ti.
[0012] In some embodiments, step S1 includes mixing the manganese-containing precursor, lithium source, W source, Nb source, and metal M source in a molar ratio of Li, Mn, W, Nb, and M of (1.001-1.2): (1.5-1.996): (0.001-0.1): (0.001-0.1): (0.001-0.1) uniformly.
[0013] In some embodiments, in step S2, the calcination temperature is 400°C to 1000°C;
[0014] In some preferred embodiments, in step S2, the calcination temperature is 600°C to 900°C;
[0015] In some embodiments, the calcination time is 5 h to 24 h.
[0016] In some preferred embodiments, the calcination time is 8 h to 20 h.
[0017] In some embodiments, the manganese-containing precursor is Mn 3 O 4 .
[0018] In some embodiments, the lithium source is one or both of active lithium carbonate and lithium hydroxide.
[0019] The second aspect of the present invention provides a positive electrode active material, which is prepared by the method disclosed in the first aspect of the present invention and has a chemical formula of Li 1+a Mn 2-a-b-c-d W b Nb c M d O 4 ;
[0020] Among them, 0.001≤a≤0.30, 0.001≤b≤0.1, 0.001≤c≤0.1, 0.001≤d≤0.1.
[0021] In some embodiments, the positive electrode active material includes a core material and a coating layer formed on the surface of the core material, wherein the coating layer includes LiNbO 3 and Li 2 WO 4 .
[0022] In some embodiments, the coating layer has a thickness of 0.1 nm to 20 nm.
[0023] The third aspect of the present invention provides a positive electrode sheet, which includes the positive electrode active material disclosed in the second aspect of the present invention.
[0024] The fourth aspect of the present invention provides a battery, which includes the positive electrode sheet disclosed in the third aspect of the present invention.
[0025] The advantages of the present invention are as follows:
[0026] The present invention can realize the combination of doping and coating through one-step calcination, has simple process, low cost and is suitable for industrial production;
[0027] The addition of metal elements can stabilize the lattice structure of lithium manganese oxide, preventing lattice distortion and structural collapse of lithium manganese oxide during charging and discharging.
[0028] During the sintering process, W and Nb elements diffuse and are evenly enriched on the surface of the material, and LiNbO is evenly formed on the surface of the material. 3 and Li 2 WO 4 The formation of these two coating layers effectively eliminates the residual Li on the surface of the material, effectively increases the capacity of the battery and improves the cycle performance of the battery. 3 and Li 2 WO 4 It has good lithium ion transmission capability, which is beneficial to improving the battery's rate performance. DETAILED DESCRIPTION
[0029] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specific implementation methods are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the description and claims of the present invention and any variations thereof are intended to cover non-exclusive inclusions.
[0031] In the description of the specific implementation methods of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present invention, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0032] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.
[0033] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present invention generally indicates that the associated objects before and after are in an "or" relationship.
[0034] Throughout the present invention, numerical values represent approximate measures or limits of ranges to cover minor deviations from given values as well as embodiments with about the values mentioned and embodiments with the exact values mentioned. Except for the working examples provided at the end of the detailed description, all numerical values of parameters (e.g., amounts or conditions) in this specification (including the appended claims) should be understood to be modified by the term "about" in all cases, regardless of whether "about" actually appears before the numerical value. "About" indicates that the stated numerical value allows some minor imprecision (close to the exact value of the value to some extent; approximately or reasonably close to the value; almost). If the imprecision provided by "about" is not otherwise understood in this ordinary sense in the art, "about" as used in the present invention at least indicates the variation that can be produced by the ordinary methods of measuring and using such parameters. For example, "about" may include a variation of less than or equal to 5%, optionally less than or equal to 4%, optionally less than or equal to 3%, optionally less than or equal to 2%, optionally less than or equal to 1%, optionally less than or equal to 0.5%, and in some aspects, optionally less than or equal to 0.1%.
[0035] Additionally, disclosure of ranges includes disclosure of all values within the entire range and further divided ranges, including endpoints and sub-ranges given for such ranges.
[0036] The preparation method of lithium manganese oxide composite materials in the prior art is generally to first dope and then coat, the process is relatively complicated, and the formed coating layer is thick and poorly uniform, which is not conducive to the capacity performance and rate performance of the battery.
[0037] In order to solve the above problems, the present invention proposes a technical solution for solving the above problems.
[0038] The first aspect of the present invention is to provide a method for preparing a positive electrode active material, the method comprising the following steps:
[0039] S1, mixing a manganese-containing precursor, a lithium source, a W source, a Nb source and a metal M source uniformly to obtain a mixture;
[0040] S2. calcining the mixture to obtain a positive electrode active material.
[0041] The invention can realize the combination of doping and coating through one-step calcination, has simple process, low cost and is suitable for industrial production.
[0042] The incorporation of metal elements can stabilize the lattice structure of lithium manganese oxide and prevent lattice distortion and structural collapse of lithium manganese oxide under the action of trivalent manganese ions.
[0043] During the sintering process, W and Nb elements diffuse and are evenly enriched on the surface of the material to dope the surface of the material, and LiNbO is evenly formed on the surface of the material. 3 and Li 2 WO 4 Coating layer: The formation of these two coating layers effectively eliminates the residual Li on the surface of the material, effectively increases the capacity of the battery and improves the cycle performance of the battery.
[0044] In some embodiments, in step S1 , the W source is tungsten oxide.
[0045] Tungsten oxide can induce the formation of oxygen vacancies on the surface of the material. The formation of surface oxygen vacancies helps the adsorption and storage of active oxygen, improves the interface stability, and thus improves the cycle stability. In addition, oxygen vacancies help reduce the energy barrier for lithium ion migration, leading to improved diffusion kinetics.
[0046] In some embodiments, in step S1 , the metal M source includes at least two metal elements.
[0047] The metal elements include at least two of Mg, Al, Ca, Ti, Cu, Zn, Y, Zr, Ru, Sn, and Sb.
[0048] The term "at least two" as used in the present invention refers to selecting two materials from the above-mentioned materials for mixing, but is not limited to two. A person skilled in the art may select a greater number. The above may be freely implemented without exceeding the scope of understanding of a person skilled in the art. The present invention does not impose any limitation on this.
[0049] In some embodiments, the metal elements include Al, Mg, Sn, and Ti.
[0050] The addition of metal elements fixes the lattice sites of lithium manganese oxide, and the doped metal elements will not change in valence with charging and discharging. Therefore, they play a supporting role inside the lithium manganese oxide, slowing down the volume change during charging and discharging, and enhancing the material's stability. The doped metal elements bond with oxygen to strengthen the metal-oxygen framework, effectively fixing the lattice oxygen of lithium manganese oxide, inhibiting the dissolution of Mn during the cycle, and extending the cycle performance of lithium manganese oxide.
[0051] In some embodiments, in step S1, a manganese-containing precursor, a lithium source, a W source, a Nb source, and a metal M source are uniformly mixed according to a molar ratio of Li, Mn, W, Nb, and M of (1.001-1.2): (1.5-1.996): (0.001-0.1): (0.001-0.1): (0.001-0.1).
[0052] In some embodiments, in step S2, the calcination temperature is 400°C to 1000°C.
[0053] In some embodiments, in step S2, the calcination time is 5 hours to 24 hours.
[0054] In specific applications, except for the temperature range endpoints of 400°C and 1000°C, any value in the above temperature range can be selected, such as 450°C, 500°C, 650°C, 680°C, 700°C, 750°C, 780°C, 800°C, 820°C, 850°C, 900°C, 950°C, etc. Except for the time endpoints of 5h and 24h, any value in the above time range can be selected, such as 6h, 8h, 10h, 15h, 20h, etc. The present invention does not impose any limitation on this.
[0055] In some preferred embodiments, in step S2, the calcination temperature is 600°C to 900°C; in some preferred embodiments, in step S2, the calcination time is 8h to 20h.
[0056] In specific applications, except for the temperature range endpoints of 600°C and 900°C, any value in the above temperature range can be selected, such as 650°C, 680°C, 700°C, 750°C, 780°C, 800°C, 820°C, 850°C, 880°C, etc. Except for the time endpoints of 8h and 20h, any value in the above time range can be selected, such as 10h, 15h, 18h, etc. The present invention does not impose any limitation on this.
[0057] In some embodiments, the manganese-containing precursor is Mn 3 O 4 .
[0058] In some embodiments, the lithium source is one or both of active lithium carbonate and lithium hydroxide.
[0059] In specific applications, the lithium source may be active lithium carbonate, lithium hydroxide, or a mixture of the two, which may be freely implemented within the scope of understanding of those skilled in the art. The present invention does not impose any limitation on this.
[0060] The second aspect of the present invention provides a positive electrode active material, which is prepared by the method disclosed in the first aspect of the present invention and has a chemical formula of Li 1+a Mn 2-a-b-c-d W b Nb c M d O 4 ;
[0061] Among them, 0.001≤a≤0.30, 0.001≤b≤0.1, 0.001≤c≤0.1, 0.001≤d≤0.1.
[0062] In some embodiments, the positive electrode active material includes a core material and a coating layer formed on the surface of the core material, wherein the coating layer includes LiNbO 3 and Li 2 WO 4 .
[0063] In some embodiments, the coating layer has a thickness of 0.1 nm to 20 nm. The coating layer formed by the migration of elements Nb and W has the advantages of being thin and uniform.
[0064] In specific applications, the specific thickness of the coating layer may be selected from 5 nm and 40 nm at the end points of the range, and may also be 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, etc. The present invention does not impose any limitation on this.
[0065] The third aspect of the present invention provides a positive electrode sheet, which includes the positive electrode active material disclosed in the second aspect of the present invention.
[0066] In some embodiments, the positive electrode sheet includes a positive electrode material layer, and the positive electrode material layer includes the positive electrode active material disclosed in the second aspect of the present invention.
[0067] In some embodiments, the positive electrode material layer further includes a binder, which improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode material layer and the positive electrode current collector.
[0068] In some embodiments, non-limiting examples of binders include polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, and the like.
[0069] In some embodiments, the cathode material layer includes a conductive agent to impart conductivity to the electrode. The conductive agent may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.
[0070] In some embodiments, the positive electrode sheet includes a positive electrode current collector. Exemplarily, the positive electrode current collector may be aluminum (Al), but is not limited thereto.
[0071] In some embodiments, based on the total mass of the positive electrode material layer, the mass percentage of the positive electrode active material particles in the positive electrode material layer is 80%-99%.
[0072] In some embodiments, the mass of the conductive agent accounts for 1%-20% of the mass of the positive electrode material layer.
[0073] In some embodiments, the mass of the binder accounts for 1%-20% of the mass of the positive electrode material layer.
[0074] In some embodiments, the positive electrode plate provided by the present invention further includes solid electrolyte powder for improving the ionic conductivity of the composite positive electrode. The present invention does not limit the type of solid electrolyte powder, which may be oxide solid electrolyte powder, sulfide solid electrolyte powder, or halide solid electrolyte powder. Optionally, the mass of the solid electrolyte powder accounts for 1%-20% of the mass of the positive electrode plate; preferably 5%-20%.
[0075] In some embodiments, the thickness of the positive electrode material layer in the positive electrode plate provided by the present invention is 30-400 μm, for example, 30 μm, 40 μm, 50 μm, 80 μm, 110 μm, 200 μm, 300 μm, 400 μm, preferably 50-110 μm.
[0076] Negative electrode:
[0077] In some embodiments, the negative electrode sheet includes a current collector and a negative active material layer disposed on the current collector.
[0078] In the present invention, the specific types of negative electrode active materials are not subject to specific restrictions and can be selected according to needs. Specifically, the negative electrode active material is selected from natural graphite, artificial graphite, mesophase microcarbon beads (abbreviated as MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO 2 , spinel-structured lithiated TiO 2 -Li 4 Ti 5 O 12 , Li-Al alloy. Non-limiting examples of carbon materials include crystalline carbon, amorphous carbon and mixtures thereof. Crystalline carbon can be amorphous or flake-shaped, platelet-shaped, spherical or fibrous natural graphite or artificial graphite. Amorphous carbon can be soft carbon, hard carbon, mesophase pitch carbide, calcined coke, etc.
[0079] In some embodiments, metal elements and metal compounds can also be selected as negative electrode active materials, such as compounds containing metals or metalloids such as Li, Ag, Al, Bi, Cu, Ga, Ge, In, Ni, Pb, Sb, Si, Sn, Sr, and Zn.
[0080] In some embodiments, the mass percentage of the negative electrode active material contained in the negative electrode active material layer may be 80%-99%, for example, 80%, 85%, 90%, 95%, 97%, 99%, etc., preferably 95%-97%.
[0081] In some embodiments, the negative electrode material layer may include a binder; the binder improves the bonding between negative electrode active material particles and the bonding between the negative electrode active material and the current collector.
[0082] In some embodiments, non-limiting examples of binders include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, and the like.
[0083] In some embodiments, the negative electrode active material layer can be obtained by coating a negative electrode slurry on a negative electrode current collector and then drying the negative electrode slurry, wherein the negative electrode slurry includes at least a negative electrode active material and a negative electrode binder. When an aqueous solvent is used as a liquid medium for forming the negative electrode slurry, a thickener is preferably used for slurrying, and the thickener can generally be used to adjust the viscosity of the slurry.
[0084] In some embodiments, the aforementioned viscosity enhancer may be one or more of the following: carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof.
[0085] In some embodiments, the mass proportion of the thickener in the negative electrode slurry can be 0.1%-5%, for example, 0.1%, 0.2%, 0.5%, 0.6%, 1%, 2%, 3%, 4%, 5%, etc., preferably 0.5%-3%, and more preferably 0.6%-2%.
[0086] In some embodiments, the negative electrode active material layer includes a conductive material so that the electrode has conductivity. The conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., such as copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.
[0087] In some embodiments, the negative electrode current collector can be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.
[0088] Diaphragm:
[0089] In some embodiments, the lithium battery and electrochemical device of the present invention are provided with a separator between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator used in the electrochemical device of the present invention are not particularly limited and can be any technology disclosed in the prior art.
[0090] In some embodiments, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present application.
[0091] In some embodiments, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film with a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide.
[0092] Electrolyte:
[0093] The lithium battery and electrochemical device of the present invention also include an electrolyte.
[0094] In some embodiments, the electrolyte includes a lithium salt and a solvent.
[0095] In some embodiments, the lithium salt includes at least one of an organic lithium salt or an inorganic lithium salt. In some embodiments, the lithium salt includes, but is not limited to: lithium hexafluorophosphate (LiPF6 ), lithium tetrafluoroborate (LiBF 4 ), lithium difluorophosphate (LiPO 2 F 2 ), bis(trifluoromethanesulfonyl)imide lithium LiN (CF 3 SO 2 ) 2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO 2 F) 2 )(LiFSI), LiB(C 2 O 4 ) 2 (LiBOB) or lithium difluorooxalatoborate LiBF 2 (C 2 O 4 )(LiDFOB).
[0096] In some embodiments, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0097] In some embodiments, the electrolyte may optionally include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.
[0098] In some embodiments, the aforementioned additives include at least one of 1,3-propane sultone, 1,4-butane sultone, propenyl-1,3-sultone, vinyl sulfate, 4-methyl vinyl sulfate, propenyl sulfate, saturated phosphate compounds and unsaturated phosphate compounds, tris(trimethylsilane) phosphate, tris(trimethylsilane) borate, tris(triethylsilane) borate, succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile, and sebaconitrile, and a compound comprising the following chemical formula:
[0099]
[0100] Among them, R 41 , R 42 , R 43 Each independently selected from a C1-C5 saturated hydrocarbon group, an unsaturated hydrocarbon group, a halogenated hydrocarbon group, -Si(C m H 2m+1 ) 3 , m is a natural number from 1 to 3, and R 41 , R 42 , R 43 At least one of them is an unsaturated hydrocarbon group.
[0101] The fourth aspect of the present invention provides a battery, which includes the positive electrode sheet disclosed in the third aspect of the present invention.
[0102] In some embodiments, the secondary battery involved in the present invention includes the above-mentioned positive electrode sheet, negative electrode sheet, separator, electrolyte, etc., but is not limited thereto.
[0103] In some embodiments, the secondary battery according to the present invention is made by stacking the above-mentioned positive and negative electrode sheets.
[0104] In some embodiments, the secondary battery of the present invention may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0105] In some embodiments, the present invention further provides a battery module. The battery module includes the above-mentioned secondary battery. The number of secondary batteries contained in the battery module of the present invention can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0106] In some embodiments, the present invention further provides a battery pack, which includes the above-mentioned battery module. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0107] The embodiments of the present invention will be described in more detail below through examples and comparative examples, wherein all examples and comparative examples are lithium ion battery sample groups prepared by the same process.
[0108] In order to intuitively and comprehensively reflect the advantages of the present invention, all embodiments and comparative examples record or perform the following tests: coating layer thickness record, 200 cycle battery capacity retention rate, and rate performance test.
[0109] It should be noted that the embodiments of the present invention are not limited to these examples.
[0110] Example 1
[0111] 1. Preparation of positive electrode active materials:
[0112] S1, the manganese-containing precursor Mn 3 O 4 、Lithium source Li 2 CO 3 、W source WO 2.72 、Nb source Nb 2 O 5 And metal oxide Al 2 O 3 , MgO are uniformly mixed according to a molar ratio of Mn, Li, W, Nb, Al, and Mg of 1.9:1:0.005:0.005:0.06:0.03 to obtain a mixture;
[0113] S2, calcining the mixture to obtain the positive electrode active material LiMn 1.9 W 0.005 Nb 0.005 Al 0.06 Mg 0.03 O 4 The calcination temperature was 680°C and the calcination time was 16 h. The thickness of the coating layer of the positive electrode active material was recorded.
[0114] 2. Preparation of positive electrode sheet:
[0115] The positive electrode active material prepared in step 1, the conductive agent Super-P, and the binder PVDF were weighed and mixed evenly in a mass ratio of 95:3:2, mixed with the solvent NMR to obtain a positive electrode slurry, and evenly coated on an aluminum foil to form a positive electrode sheet.
[0116] 3. Preparation of negative electrode sheet:
[0117] The negative electrode active material graphite, conductive agent Super-P, binder CMC, and SBR were weighed and mixed evenly in a mass ratio of 95:3:1:1, mixed with solvent deionized water to obtain a negative electrode slurry, and evenly coated on a copper foil to form a negative electrode sheet.
[0118] 4. Preparation of batteries:
[0119] The positive electrode sheet prepared in step 2, the negative electrode sheet prepared in step 3 and the separator are assembled, and the electrolyte is injected to form a battery.
[0120] Embodiment 2:
[0121] 1. Preparation of positive electrode active materials:
[0122] S1, the manganese-containing precursor Mn 3 O 4 、Lithium source Li2 CO 3 、W source WO 2.72 、Nb source Nb 2 O 5 And metal oxide Al 2 O 3 , MgO are uniformly mixed according to a molar ratio of Mn, Li, W, Nb, Al, and Mg of 1.908:1:0.001:0.001:0.06:0.03 to obtain a mixture;
[0123] S2, calcining the mixture to obtain the positive electrode active material LiMn 1.908 W 0.001 Nb 0.001 Al 0.06 Mg 0.03 O 4 The calcination temperature was 680°C and the calcination time was 16 h. The thickness of the coating layer of the positive electrode active material was recorded.
[0124] 2. Preparation of positive electrode sheet:
[0125] The positive electrode active material prepared in step 1, the conductive agent Super-P, and the binder PVDF were weighed and mixed evenly in a mass ratio of 95:3:2, mixed with the solvent NMR to obtain a positive electrode slurry, and evenly coated on an aluminum foil to form a positive electrode sheet.
[0126] 3. Preparation of negative electrode sheet:
[0127] The negative electrode active material graphite, conductive agent Super-P, binder CMC, and SBR were weighed and mixed evenly in a mass ratio of 95:3:1:1, mixed with solvent deionized water to obtain a negative electrode slurry, and evenly coated on a copper foil to form a negative electrode sheet.
[0128] 5. Preparation of batteries:
[0129] The positive electrode sheet prepared in step 2, the negative electrode sheet prepared in step 3 and the separator are assembled, and the electrolyte is injected to form a battery.
[0130] Embodiment 3:
[0131] 1. Preparation of positive electrode active materials:
[0132] S1, the manganese-containing precursor Mn 3 O 4 、Lithium source Li 2 CO 3 、W source WO 2.72 、Nb source Nb 2 O 5 And metal oxide Al 2 O 3, MgO are uniformly mixed according to a molar ratio of Mn, Li, W, Nb, Al, and Mg of 1.71:1:0.1:0.1:0.06:0.03 to obtain a mixture;
[0133] S2, calcining the mixture to obtain the positive electrode active material LiMn 1.71 W 0.1 Nb 0.1 Al 0.06 Mg 0.03 O 4 The calcination temperature was 680°C and the calcination time was 16 h. The thickness of the coating layer of the positive electrode active material was recorded.
[0134] 2. Preparation of positive electrode sheet:
[0135] The positive electrode active material prepared in step 1, the conductive agent Super-P, and the binder PVDF were weighed and mixed evenly in a mass ratio of 95:3:2, mixed with the solvent NMR to obtain a positive electrode slurry, and evenly coated on an aluminum foil to form a positive electrode sheet.
[0136] 3. Preparation of negative electrode sheet:
[0137] The negative electrode active material graphite, conductive agent Super-P, binder CMC, and SBR were weighed and mixed evenly in a mass ratio of 95:3:1:1, mixed with solvent deionized water to obtain a negative electrode slurry, and evenly coated on a copper foil to form a negative electrode sheet.
[0138] 4. Preparation of batteries:
[0139] The positive electrode sheet prepared in step 2, the negative electrode sheet prepared in step 3 and the separator are assembled, and the electrolyte is injected to form a battery.
[0140] Embodiment 4:
[0141] 1. Preparation of positive electrode active materials:
[0142] S1, the manganese-containing precursor Mn 3 O 4 、Lithium source Li 2 CO 3 、W source WO 2.72 、Nb source Nb 2 O 5 And metal oxide Al 2 O 3 , MgO are uniformly mixed according to the molar ratio of Mn, Li, W, Nb, Al and Ti of 1.81:1:0.05:0.05:0.06:0.015 to obtain a mixture;
[0143] S2, calcining the mixture to obtain the positive electrode active material LiMn 1.81 W0.05 Nb 0.05 Al 0.06 Ti 0.015 O 4 The calcination temperature was 680°C and the calcination time was 16 h. The thickness of the coating layer of the positive electrode active material was recorded.
[0144] 2. Preparation of positive electrode sheet:
[0145] The positive electrode active material prepared in step 1, the conductive agent Super-P, and the binder PVDF were weighed and mixed evenly in a mass ratio of 95:3:2, mixed with the solvent NMR to obtain a positive electrode slurry, and evenly coated on an aluminum foil to form a positive electrode sheet.
[0146] 3. Preparation of negative electrode sheet:
[0147] The negative electrode active material graphite, conductive agent Super-P, binder CMC, and SBR were weighed and mixed evenly in a mass ratio of 95:3:1:1, mixed with solvent deionized water to obtain a negative electrode slurry, and evenly coated on a copper foil to form a negative electrode sheet.
[0148] 4. Preparation of batteries:
[0149] The positive electrode sheet prepared in step 2, the negative electrode sheet prepared in step 3 and the separator are assembled, and the electrolyte is injected to form a battery.
[0150] Example 5
[0151] 1. Preparation of positive electrode active materials:
[0152] S1, the manganese-containing precursor Mn 3 O 4 、Lithium source Li 2 CO 3 , W source sodium tungstate, Nb source Nb 2 O 5 And metal oxide Al 2 O 3 , MgO are uniformly mixed according to a molar ratio of Mn, Li, W, Nb, Al, and Mg of 1.9:1:0.005:0.005:0.06:0.03 to obtain a mixture;
[0153] S2, calcining the mixture to obtain the positive electrode active material LiMn 1.9 W 0.005 Nb 0.005 Al 0.06 Mg 0.03 O 4 The calcination temperature was 680°C and the calcination time was 16 h. The thickness of the coating layer of the positive electrode active material was recorded.
[0154] 2. Preparation of positive electrode sheet:
[0155] The positive electrode active material prepared in step 1, the conductive agent Super-P, and the binder PVDF were weighed and mixed evenly in a mass ratio of 95:3:2, mixed with the solvent NMR to obtain a positive electrode slurry, and evenly coated on an aluminum foil to form a positive electrode sheet.
[0156] 3. Preparation of negative electrode sheet:
[0157] The negative electrode active material graphite, conductive agent Super-P, binder CMC, and SBR were weighed and mixed evenly in a mass ratio of 95:3:1:1, mixed with solvent deionized water to obtain a negative electrode slurry, and evenly coated on a copper foil to form a negative electrode sheet.
[0158] 6. Preparation of batteries:
[0159] The positive electrode sheet prepared in step 2, the negative electrode sheet prepared in step 3 and the separator are assembled, and the electrolyte is injected to form a battery.
[0160] The difference between this embodiment and embodiment 1 is that the W source is sodium tungstate.
[0161] Example 6
[0162] 1. Preparation of positive electrode active materials:
[0163] S1, the manganese-containing precursor Mn 3 O 4 、Lithium source Li 2 CO 3 、W source WO 2.72 、Nb source Nb 2 O 5 And metal oxide Al 2 O 3 The molar ratio of Mn, Li, W, Nb and Al is 1.93:1:0.005:0.005:0.06. Mix well to obtain a mixture;
[0164] S2, calcining the mixture to obtain the positive electrode active material LiMn 1.93 W 0.005 Nb 0.005 Al 0.06 O 4 The calcination temperature was 680°C and the calcination time was 16 h. The thickness of the coating layer of the positive electrode active material was recorded.
[0165] 2. Preparation of positive electrode sheet:
[0166] The positive electrode active material prepared in step 1, the conductive agent Super-P, and the binder PVDF were weighed and mixed evenly in a mass ratio of 95:3:2, mixed with the solvent NMR to obtain a positive electrode slurry, and evenly coated on an aluminum foil to form a positive electrode sheet.
[0167] 3. Preparation of negative electrode sheet:
[0168] The negative electrode active material graphite, conductive agent Super-P, binder CMC, and SBR were weighed and mixed evenly in a mass ratio of 95:3:1:1, mixed with solvent deionized water to obtain a negative electrode slurry, and evenly coated on a copper foil to form a negative electrode sheet.
[0169] 4. Preparation of batteries:
[0170] The positive electrode sheet prepared in step 2, the negative electrode sheet prepared in step 3 and the separator are assembled, and the electrolyte is injected to form a battery.
[0171] Comparative Example 1
[0172] 1. Preparation of positive electrode active materials:
[0173] S1, the manganese-containing precursor Mn 3 O 4 、Lithium source Li 2 CO 3 、Nb source Nb 2 O 5 And metal oxide Al 2 O 3 and MgO are uniformly mixed according to a molar ratio of Mn, Li, Nb, Al, and Mg of 1.905:1:0.005:0.06:0.03 to obtain a mixture;
[0174] S2. The mixture is calcined to obtain a positive electrode active material. The calcination temperature is 680° C. and the calcination time is 16 h. The thickness of the coating layer of the positive electrode active material is recorded.
[0175] 2. Preparation of positive electrode sheet:
[0176] The positive electrode active material prepared in step 1, the conductive agent Super-P, and the binder PVDF were weighed and mixed evenly in a mass ratio of 95:3:2, mixed with the solvent NMR to obtain a positive electrode slurry, and evenly coated on an aluminum foil to form a positive electrode sheet.
[0177] 3. Preparation of negative electrode sheet:
[0178] The negative electrode active material graphite, conductive agent Super-P, binder CMC, and SBR were weighed and mixed evenly in a mass ratio of 95:3:1:1, mixed with solvent deionized water to obtain a negative electrode slurry, and evenly coated on a copper foil to form a negative electrode sheet.
[0179] 4. Preparation of batteries:
[0180] The positive electrode sheet prepared in step 2, the negative electrode sheet prepared in step 3 and the separator are assembled, and the electrolyte is injected to form a battery.
[0181] Comparative Example 2
[0182] 1. Preparation of positive electrode active materials:
[0183] S1, the manganese-containing precursor Mn 3 O 4 、Lithium source Li 2 CO 3 、W source WO 2.72 And metal oxide Al 2 O 3 , MgO are uniformly mixed according to a molar ratio of Mn, Li, W, Al, and Mg of 1.905:1:0.005:0.06:0.03 to obtain a mixture;
[0184] S2. The mixture is calcined to obtain a positive electrode active material. The calcination temperature is 680° C. and the calcination time is 16 h. The thickness of the coating layer of the positive electrode active material is recorded.
[0185] 2. Preparation of positive electrode sheet:
[0186] The positive electrode active material prepared in step 1, the conductive agent Super-P, and the binder PVDF were weighed and mixed evenly in a mass ratio of 95:3:2, mixed with the solvent NMR to obtain a positive electrode slurry, and evenly coated on an aluminum foil to form a positive electrode sheet.
[0187] 3. Preparation of negative electrode sheet:
[0188] The negative electrode active material graphite, conductive agent Super-P, binder CMC, and SBR were weighed and mixed evenly in a mass ratio of 95:3:1:1, mixed with solvent deionized water to obtain a negative electrode slurry, and evenly coated on a copper foil to form a negative electrode sheet.
[0189] 4. Preparation of batteries:
[0190] The positive electrode sheet prepared in step 2, the negative electrode sheet prepared in step 3 and the separator are assembled, and the electrolyte is injected to form a battery.
[0191] Comparative Example 3
[0192] 1. Preparation of positive electrode active materials:
[0193] S1, the manganese-containing precursor Mn 3 O 4 、Lithium source Li 2 CO 3、 Metal oxide Al 2 O 3 and MgO are uniformly mixed according to a molar ratio of Mn, Li, Al, and Mg of 1.91:1:0.06:0.03 to obtain a mixture;
[0194] S2. The mixture is calcined to obtain a positive electrode active material. The calcination temperature is 680° C. and the calcination time is 16 h. The thickness of the coating layer of the positive electrode active material is recorded.
[0195] 2. Preparation of positive electrode sheet:
[0196] The positive electrode active material prepared in step 1, the conductive agent Super-P, and the binder PVDF were weighed and mixed evenly in a mass ratio of 95:3:2, mixed with the solvent NMR to obtain a positive electrode slurry, and evenly coated on an aluminum foil to form a positive electrode sheet.
[0197] 3. Preparation of negative electrode sheet:
[0198] The negative electrode active material graphite, conductive agent Super-P, binder CMC, and SBR were weighed and mixed evenly in a mass ratio of 95:3:1:1, mixed with solvent deionized water to obtain a negative electrode slurry, and evenly coated on a copper foil to form a negative electrode sheet.
[0199] 4. Preparation of batteries:
[0200] The positive electrode sheet prepared in step 2, the negative electrode sheet prepared in step 3 and the separator are assembled, and the electrolyte is injected to form a battery.
[0201] Comparative Example 4
[0202] 1. Preparation of positive electrode active materials:
[0203] S1, the manganese-containing precursor Mn 3 O 4 、Lithium source Li 2 CO 3 、W source WO 2.72 、Nb source Nb 2 O 5 Mn, Li, W, and Nb are uniformly mixed in a molar ratio of 1.99:1:0.005:0.005 to obtain a mixture;
[0204] S2. The mixture is calcined to obtain a positive electrode active material. The calcination temperature is 680° C. and the calcination time is 16 h. The thickness of the coating layer of the positive electrode active material is recorded.
[0205] 2. Preparation of positive electrode sheet:
[0206] The positive electrode active material prepared in step 1, the conductive agent Super-P, and the binder PVDF were weighed and mixed evenly in a mass ratio of 95:3:2, mixed with the solvent NMR to obtain a positive electrode slurry, and evenly coated on an aluminum foil to form a positive electrode sheet.
[0207] 3. Preparation of negative electrode sheet:
[0208] The negative electrode active material graphite, conductive agent Super-P, binder CMC, and SBR were weighed and mixed evenly in a mass ratio of 95:3:1:1, mixed with solvent deionized water to obtain a negative electrode slurry, and evenly coated on a copper foil to form a negative electrode sheet.
[0209] 4. Preparation of batteries:
[0210] The positive electrode sheet prepared in step 2, the negative electrode sheet prepared in step 3 and the separator are assembled, and the electrolyte is injected to form a battery.
[0211] Comparative experiment:
[0212] The batteries of Examples 1-6 and Comparative Examples 1-4 were tested as follows.
[0213] 1. 200 cycles battery capacity retention test:
[0214] At a temperature of 45°C, charge at a current of 0.2C to a charging cut-off voltage of 4.2V, switch to constant voltage charging to a cut-off current of 0.05C, let stand for 0.5h, discharge at a current of 0.2C to a cut-off voltage of 3.0V, let stand for 0.5h, enter the next charge and discharge cycle, and so on, for a total of 200 charge and discharge cycles, 200 cycle retention rate = discharge capacity of the battery at the 200th cycle / first discharge capacity.
[0215] 2. Rate performance test:
[0216] At a temperature of 45°C, the fully charged battery is discharged at a current of 0.1C to a cut-off voltage of 3.0V, and the capacity obtained by the test is C0;
[0217] At a temperature of 45°C, a fully charged battery is discharged at a current of 3C to a cut-off voltage of 3.0V. The capacity obtained by the test is C1, and C1 / C0 is the 3C discharge capacity retention rate below.
[0218] 3. Coating thickness test:
[0219] Using a TEM electron microscope, ten different locations were selected to measure the thickness and the average value was taken.
[0220] The test results are summarized in the following table.
[0221]
[0222]
[0223] According to the above table:
[0224] Comparative Example 1 with Comparative Example 3 and Comparative Example 4: In Example 1, the cycle performance and rate performance of the battery are effectively improved by doping lithium manganese oxide with multiple elements and co-coating with W and Nb. The possible reason is that the lattice structure of lithium manganese oxide is effectively stabilized by doping with multiple elements, and the contact between the electrolyte and lithium manganese oxide is effectively isolated by coating, thereby effectively eliminating excess lithium on the surface of lithium manganese oxide.
[0225] Comparison of Example 1 with Comparative Example 1 and Comparative Example 2: Example 1 uses W and Nb for coordinated coating, which effectively improves the cycle performance and rate performance of the battery compared to coating each separately.
[0226] Comparison of Example 1 and Example 5: The positive electrode active material prepared in Example 1 using tungsten oxide as a tungsten source has better cycle stability and lithium ion transport capacity. The possible reason is that tungsten oxide can induce the formation of oxygen vacancies on the surface of the material. The formation of surface oxygen vacancies helps the adsorption and storage of active oxygen, improves the interface stability, and thus improves the cycle stability. Oxygen vacancies help reduce the energy barrier to lithium ion migration, leading to improved diffusion kinetics.
[0227] Comparison between Example 1 and Example 6: In Example 1, multi-metal element doping is used, which is more beneficial to improving the stability of the positive electrode active material than single metal element doping.
[0228] The above is only a possible speculation on the mechanism of the technical solution of the present application and does not constitute a limitation on the protection scope of the present application.
[0229] It should be pointed out that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a positive electrode active material, characterized in that: The steps include: S1, mixing a manganese-containing precursor, a lithium source, a W source, a Nb source and a metal M source uniformly to obtain a mixture; S2. calcining the mixture to obtain a positive electrode active material.
2. The method according to claim 1, characterized in that: In the step S1, the W source is tungsten oxide.
3. The method according to claim 1, characterized in that In the step S1, the metal M source includes at least two metal elements M; The metal element M includes at least two of Mg, Al, Ca, Ti, Cu, Zn, Y, Zr, Ru, Sn, and Sb.
4. The method according to claim 3, characterized in that The metal elements M include at least two of Al, Mg, Sn, and Ti.
5. The method according to claim 1, characterized in that: The step S1 includes uniformly mixing a manganese-containing precursor, a lithium source, a W source, a Nb source, and a metal M source according to a molar ratio of Li, Mn, W, Nb, and M of (1.001-1.2): (1.5-1.996): (0.001-0.1): (0.001-0.1): (0.001-0.1).
6. The method according to claim 1, characterized in that In step S2, the calcination temperature is 400° C. to 1000° C.; and / or, The calcination time is 5 hours to 24 hours.
7. A positive electrode active material prepared by the method according to any one of claims 1 to 6; characterized in that: The chemical formula of the positive electrode active material is Li 1+a Mn 2-a-b-c-d W b Nb c M d O4; Among them, 0.001≤a≤0.30, 0.001≤b≤0.1, 0.001≤c≤0.1, 0.001≤d≤0.
1.
8. The positive electrode active material according to claim 7, characterized in that The positive electrode active material includes a core material and a coating layer formed on the surface of the core material, and the coating layer includes LiNbO3 and Li2WO4. 9 . A positive electrode sheet comprising the positive electrode active material according to claim 8 .
10. A battery comprising the positive electrode sheet according to claim 9.
Citation Information
Patent Citations
Anode material of lithium ion battery and preparation method thereof
CN102394290A
Doped and coated single crystal positive electrode material and method for doping and coating single crystal positive electrode material
CN111697221A
Monocrystal lithium manganate positive electrode material and preparation method thereof
CN113285068A
Positive electrode material and preparation method and application thereof
CN116779826A
Multifunctional-layer lithium manganate positive electrode material, preparation method thereof, positive electrode plate and battery
CN119008931A